Barriers to self-monitoring of blood glucose among adults with diabetes in an HMO: A cross sectional study - Adams, Alyce S (BioMed Central, 2003)
BACKGROUND: Recent studies suggest that patients at greatest risk for diabetes complications are least likely to self-monitor blood glucose. However, these studies rely on self-reports of monitoring, an unreliable measure of actual behavior. The purpose of the current study was to examine the relationship between patient characteristics and self-monitoring in a large health maintenance organization (HMO) using test strips as objective measures of self-monitoring practice. METHODS: This cross-sectional study included 4,565 continuously enrolled adult managed care patients in eastern Massachusetts with diabetes. Any self-monitoring was defined as filling at least one prescription for self-monitoring test strips during the study period (10/1/92–9/30/93). Regular SMBG among test strip users was defined as testing an average of once per day for those using insulin and every other day for those using oral sulfonylureas only. Measures of health status, demographic data, and neighborhood socioeconomic status were obtained from automated medical records and 1990 census tract data. RESULTS: In multivariate analyses, lower neighborhood socioeconomic status, older age, fewer HbA1c tests, and fewer physician visits were associated with lower rates of self-monitoring. Obesity and fewer comorbidities were also associated with lower rates of self-monitoring among insulin-managed patients, while black race and high glycemic level (HbA1c>10) were associated with less frequent monitoring. For patients taking oral sulfonylureas, higher dose of diabetes medications was associated with initiation of self-monitoring and HbA1c lab testing was associated with more frequent testing. CONCLUSIONS: Managed care organizations may face the greatest challenges in changing the self-monitoring behavior of patients at greatest risk for poor health outcomes (i.e., the elderly, minorities, and people living in low socioeconomic status neighborhoods).